The Effect of The Project-Based Learning Model With a Multimodal Approach on Students’ Understanding of Physics Concepts - Windy Zaerani; Gunawan Gunawan; Kosim Kosim (Indonesian Publication Center, 2026)
This study aims to analyze the effect of the project-based learning model with a multimodal approach on students' understanding of physics concepts. Using a quasi-experimental method with a Non-equivalent Control Group Design, the research was conducted at SMAN 7 Mataram for class XI in the even semester of 2025/2026. Samples were selected using purposive sampling, consisting of class XI A3 (experimental, n=30) and class XI A2 (control, n=29). The instrument consisted of 20 valid and reliable multiple-choice questions (r11 of 0,934). The results showed that the average posttest score of the experimental class (81) was significantly higher than the control class (70). The Independent Sample T-test showed a significant difference with = 2,328 > = 2,002 at a 5% significance level. It is concluded that the implementation of the project-based learning model with a multimodal approach has a significant effect on improving students' understanding of physics concepts.